International cooperation on migration policy: Dare to to more! The Global Forum on Migration and Development in Berlin opens up opportunities - Steffen Angenendt; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2017)
Germany and Morocco are currently joint chair of the Global Forum on Migration and Development (GFMD). This year's meeting will take place in June 2017 in Berlin. The Forum is more important than ever: refugee and migrant numbers are on the increase; the lines between forced and voluntary migration are becoming increasingly blurred; and governments are less and less able to cope with the associated challenges on their own. And yet international cooperation on migration policy is weak, fragmented and mostly ineffective. The Berlin conference can make a contribution to strengthening it. The meeting also offers the German Federal Government an excellent opportunity for extending its role in shaping international cooperation on migration policy.
Keywords: 320